Microcontroller and Android HMI Based Water Level and Control System - Lestariningsih, Tri; Artono, Budi; Asyik Hidayatullah, Nur; Kusbandono, Hendrik (EAI Endorsed Transactions on Internet of Things, 2019)
Water is a basic human need in daily life. The use of water is used for various household needs for example for consumption, bathing, washing and so on. At present there are still many people who use water pumps to fill water reservoirs at home or in office buildings that are filled manually, so that problems often occur such as the level of water in the reservoir where water is unknown, it is possible that the situation of reservoirs can occur overflow or empty. Utilizing technology in this research will create a tool used to control the water level in the reservoir, which is "Microcontroller-Based Water Level Control System and Android HMI" which is an alternative in controlling and monitoring the water level in a reservoir automatically using an Android Smartphone. This tool is used to control and monitor water reservoirs automatically via Android HMI so that it can be controlled remotely. This tool is designed using a NodeMCU ESP8266 Microcontroller, a relay module that functions to turn on and turn off the pump, and one sensor, the HC-SR04 Ultrasonic Sensor which functions to measure the water level in the reservoir. And the android application used is Cayenne. The test result data is shown in the cayenne application in the form of setting the water height setpoint, the ON / OFF pump indicator and the height value in units of percent (%) and centimeter (cm).
Keywords: Water Level Control; Mikrokontroler; NodeMCU ESP8266; Android HMI; Cayenne